2010
DOI: 10.1002/jbmr.300
|View full text |Cite
|
Sign up to set email alerts
|

The calcium-sensing receptor mediates bone turnover induced by dietary calcium and parathyroid hormone in neonates

Abstract: We have investigated, in neonates, whether the calcium-sensing receptor (CaR) mediates the effects of dietary calcium on bone turnover and/or modulates parathyroid hormone (PTH)–induced bone turnover. Wild-type (WT) pups and pups with targeted deletion of the Pth (Pth–/–) gene or of both Pth and CaR (Pth–/–CaR–/–) genes were nursed by dams on a normal or high-calcium diet. Pups nursed by dams on a normal diet received daily injections of vehicle or of PTH(1–34) (80 µg/kg) for 2 weeks starting from 1 week of ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 55 publications
4
26
1
Order By: Relevance
“…Our results examining TRAP-positive osteoclast numbers and surface in the 2-wk-old pups with varying levels of calcium and 1,25(OH) 2 D 3 suggest that the absence of the bone-resorbing activity of 1,25(OH) 2 D 3 may supersede any effect of calcium on bone resorption, and in fact calcium supplementation in the 2-wk-old mice may inhibit osteoclastic bone resorption, as we reported previously (38), either directly (22), indirectly, or both. Thus, calcitonin release in rodents has been implicated in bone sparing in lactating females (43) and could help explain the reduced osteoclasts in the pups with elevations in calcium.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Our results examining TRAP-positive osteoclast numbers and surface in the 2-wk-old pups with varying levels of calcium and 1,25(OH) 2 D 3 suggest that the absence of the bone-resorbing activity of 1,25(OH) 2 D 3 may supersede any effect of calcium on bone resorption, and in fact calcium supplementation in the 2-wk-old mice may inhibit osteoclastic bone resorption, as we reported previously (38), either directly (22), indirectly, or both. Thus, calcitonin release in rodents has been implicated in bone sparing in lactating females (43) and could help explain the reduced osteoclasts in the pups with elevations in calcium.…”
Section: Discussionsupporting
confidence: 64%
“…More recent studies have reported that deletion of the Casr gene in osteoblasts profoundly blocked postnatal growth and skeletal development, a finding that was evident by 3 days of age (5). Our recent study has demonstrated that CaR deficiency abolishes skeletal responses to dietary calcium supplementation in suckling neonates (38) and suggests that raising serum calcium concentration by dietary calcium supplementation may activate CaR and subsequently produce a skeletal anabolic action, at least in the neonates. Taken together, these data suggest that 1,25(OH) 2 D 3 and calcium can each exert cooperative roles on osteoblastic bone formation in the neonate.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, since bone formation is increased in the CaSR−/−, probably because of hyperparathyroidism, reduced in the PTH−/−, and markedly reduced in the CaSR−/−PTH−/−, it can be inferred that CaSR plays a stimulatory effect on osteoblast function, as observed in previous cell culture experiments [11,19]. Additional studies performed in wild-type, PTH−/− and CaSR−/ −PTH−/− pups fed a normal diet or high-calcium diet or treated with PTH have shown that CaSR is essential in mediating the alterations in bone turnover following changes in dietary calcium and the PTH-induced modifications in bone turnover [64].…”
Section: Casr-mediated Effects In Cultured Chondrocytesmentioning
confidence: 80%
“…Previously, we reported a skeletal anabolic effect for CaSR in neonates in association with daily exogenous PTH administration (43). These studies suggest a skeletal anabolic role for CaSR in the fetus and neonate independent of its role of maintaining calcium homeostasis in adult animals.…”
Section: E849mentioning
confidence: 99%
“…In contrast, mice with osteoblast-specific deletion of CaSR exhibit undermineralized skeletons (5). CaSR also mediates alterations in bone turnover in murine neonates in response to changes in dietary calcium and modulates PTH-stimulated bone turnover, which is required for bone anabolism (43). In adult mouse models we recently provided evidence that the absence of [Ca 2ϩ ] e -stimulated CaSR activity reduces bone resorption (37), and we (30) and others (11) have provided evidence in vivo in rodent models for the effect of an allosteric activator of CaSR, cinacalcet, to increase the number and activity of osteoclasts.…”
mentioning
confidence: 99%